Bounded and Shielded: Assessing Security Aspects and Trustworthiness of Smart Contracts - Batista, Danielle; Lemieux, Victoria (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
This is an in-progress research project that aims to explore how archival science and cybersecurity can be applied to evaluate the trustworthiness and security of smart contracts. The analysis will be made using the requirements of trustworthy records and the investigation of vulnerabilities related to the development and implementation of smart contracts. The expected contribution is to improve smart contracts’ trustworthiness as archival records and evidence.